1994
DOI: 10.1515/hfsg.1994.48.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Wood-Wetting Process

Abstract: The analysis of water-wetting of wood was performed. Basic characteristics for wetting process were defined and determined experimentally -the contact angle at the beginning of wetting 0 and the equilibrium contact angle 0 U . Based on these characteristics, the contact angle, signed äs 0 W , corresponding to ideal smooth wood surface was determined. The results were used for the computation of free wood -surface energy and compared with the data from literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 6 publications
3
49
0
1
Order By: Relevance
“…The analysis was made in the temperature range 20-260°C by the use of open platinum crucibles, helium flow 2 dm 3 /h and heating rate 5°C/min. The adhesive properties of the investigated resin mixture were determined by evaluating the interactions occurring on the wood-adhesive phase boundary: the contact angle was determined by means of the method described by, among others, Liptàkovà and Kúdela (1994Kúdela ( , 2002, Kúdela and Liptáková (2006). To prepare the samples for investigations, the prepared adhesive mixture was applied on one side of the birch boards at a spread rate of 160 g/m 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was made in the temperature range 20-260°C by the use of open platinum crucibles, helium flow 2 dm 3 /h and heating rate 5°C/min. The adhesive properties of the investigated resin mixture were determined by evaluating the interactions occurring on the wood-adhesive phase boundary: the contact angle was determined by means of the method described by, among others, Liptàkovà and Kúdela (1994Kúdela ( , 2002, Kúdela and Liptáková (2006). To prepare the samples for investigations, the prepared adhesive mixture was applied on one side of the birch boards at a spread rate of 160 g/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In these calculations, based on the data from literature, the following values were employed for free surface energy of water (Liptáková and Kúdela 1994):…”
Section: Methodsmentioning
confidence: 99%
“…With respect to this, obtained results should be regarded with caution in their absolute value, but it should be noted that the objective of this study is to demonstrate the machined of woods surfaces with differently machined processes, so this approach seems to be suitable. Different methods for the determination of equilibrium contact angle that can be used to calculate the surface free energy of wood have been presented (Cao et al 2005;Gindl et al 2004;Jennings et al 2006;Liptakova and Kudela 1994). In this study, the relative equilibrium contact angle (which is the intercept value of the regress line of contact angle values over time, the value at t = 0 was taken to simulate the value of the equilibrium contact angle) was utilized to calculate the surface free energy of the wood samples, because many authors had indicated that the contact angle obtained by this method could evaluated the surface free energy of wood material successfully (Cao et al 2005;Cao and Kamdem 2007;Maldas and Kamdem 1998;Mamiński et al 2009;Nzokou and Kamdem 2004).…”
Section: Determination Of Surface Free Energy Componentsmentioning
confidence: 99%
“…Because both the absorption and spreading occur simultaneously, care must be taken to separate these processes. Different methods for determination of equilibrium contact angle and the contact angle used to calculate the surface free energy of wood have been presented (Liptakova and Kudela 1994). In this study, contact angle evolution after the initial wetting was fitted with a linear function, as we assumed that at the transient time of 0 to 0.5 s, spreading is forceful compared with absorption of samples; after that, the spreading and absorption are synchronous, and the function was extrapolated to t = 0.…”
Section: Contact Angle Measurementmentioning
confidence: 99%
“…These characteristics have been studied recently and in the past (Gardner et al 1991;Liptakova et al 1995;Liu et al 1998;de Meijer et al 2000;Wålinder and Strom 2001;Gindl and Tschegg 2002). Contact angle is the most commonly applied method to calculate surface free energy data for solids using various reference liquids, with several different approaches (Fowkes and Mostafa 1978;Liptakova and Kudela 1994;Gindl et al 2001a,b). Many theories have been introduced to describe and measure the surface free energy of materials with applications to wood systems.…”
Section: Introductionmentioning
confidence: 99%